2022
DOI: 10.1128/aac.01703-21
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Omadacycline in Rat Methicillin-Resistant Staphylococcus aureus Osteomyelitis

Abstract: Omadacycline, vancomycin and rifampin as well as rifampin combination therapies were evaluated in an experimental rat model of MRSA osteomyelitis. All treatment groups had less MRSA recovered than saline-treated animals. Emergence of rifampin resistance was observed in 3 of 16 animals with rifampin monotherapy, and none with rifampin combination therapy. After treatment, the median tibial bacterial load was 6.04, 0.1, 4.81 and 5.24 log 10 cfu/g for saline-, rifampin-, vancomycin- and om… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Furthermore, newer antibiotics that did not appear in our search at the time of the study should be evaluated for their potential intracellular effectiveness. For example, omadacycline, a novel tetracycline, seems to be effective against MRSA in osteomyelitis in a mouse model 188 and intracellularly against Legionella pneumophila, 189 even though its effectiveness seems to be pH dependent. 190 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, newer antibiotics that did not appear in our search at the time of the study should be evaluated for their potential intracellular effectiveness. For example, omadacycline, a novel tetracycline, seems to be effective against MRSA in osteomyelitis in a mouse model 188 and intracellularly against Legionella pneumophila, 189 even though its effectiveness seems to be pH dependent. 190 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, many researchers have used rat models to explore the therapeutic effect of antibiotics on MRSA-induced osteomyelitis [ 52 , 53 , 54 ]. For instance, Karau et al compared the efficacy of rifabutin, rifapentine, and rifampin, alone or in combination with vancomycin, in the treatment of foreign body osteomyelitis in rats [ 52 ].…”
Section: Osteomyelitis/bone Infectionsmentioning
confidence: 99%
“…This suggests that rifapentine and/or rifabutin might be an alternative to rifampin in the clinical management of S. aureus -caused periprosthetic joint infections. Karau et al reported that omadacycline exhibited activity in a rat model of chronic osteomyelitis induced by MRSA when it was administered alone, and higher activity when administered with rifampin [ 53 ]. Zhou et al found that the combination of erythromycin and curcumin was able to inhibit the growth of MRSA and reduce bone infections in rats [ 54 ].…”
Section: Osteomyelitis/bone Infectionsmentioning
confidence: 99%